Pengembangan Media Kartu Notasi Angka Pada Pembelajaran Sbdp Kelas IV Di SD Katolik Sang Timur Malang - Maria Marselina Peni; Andika Gutama (CV. ITTC INDONESIA, 2024)
The lack of media and learning resources in the arts and culture curriculum related to music art results in low student learning motivation, which is the main driver of this study. This study aims to elucidate the process of creating number notation card media, assess its feasibility, and verify its usefulness. The study employs a research and development (R&D) approach, using the 4-D model (Define, Design, Development, and Dissemination). The research participants were fourth-grade students at SDK Sang Timur Malang. Acceptability is achieved through a validation sheet that includes media, content, and language experts. Teachers and students' questionnaire responses serve as a tool for rotating practicality. The data analysis process includes the use of qualitative and quantitative descriptive methodologies. Material experts have gathered information from validation tests conducted by language, media, and material experts. Material, mediMaterial, media, and language experts received scores of 90%, 93%, and 85% respectively, all of which satisfied the